EKOSOSIALISME Mengungkap Kembali Pemikiran Ekonomi-Politik Lingkungan Ernst Friedrich Schumacher - , ANDREAS BUDI WIDYANTA; , Prof. Dr. Susetiawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Multidimensional crisis caused by neoliberal economic globalization has led to genocide, ethnocide, and ecocide as well. Such emergency situation has been a deep concern of many people. For example, in recent years, transnational corporations as new leviathan continues to drive many resources exploitation (living and non-living), deforestration, and remove the indigenous people from their lands. The issue of globalization and neoliberalism, that are despotic and hegemonic, has indirectly triggered \"the return of Schumacher thought\" in the intellectual world. For nearly four decades, the thinking of E.F. Schumacher was absent in the academic discourse in Indonesia. Although once very famous with his Small is Beautiful, his critical thinking to capitalism has not been explored specifically in detail by Indonesian academic. Basically, this study has two main objectives: first, this research aims to uncover the depth of the Schumacherâs thought on politics, economics and environment as a central contributor to the paradigm and praxis of Eco-socialism, and more particularly of Eco-localism. Second, in the Indonesian context, the study will reveal the contribution of Schumacherâs thinking to the discipline of sociology and to the alternative model of Indonesia development. The study seeks to re-invent the significance of Schumacherâs thoughts on politics, economics, and environment that contribute to the search for alternative solutions to the multidimensional crisis. Schumacher radical critique of the paradigm of modern economics and all their practices that glorified gigantic economic growth, known as Economism âalong with its destructive impacts on various aspects of life, has spawned a \"new economics\" that prioritizes the small people and the environment. Schumacher called it: \"An Economics of Permanence\", reffering to Economics that is pro poor and pro ecology as well . The idea of \" Economics of Permanence \" -explored in the âSmall is Beautifulâ- has contributed a significant effect on the paradigm of Eco-socialism movement. As the main notion that opposed to the gigantic power of market fundamentalism regime, Ecosocialism has many braches of its idea, one of the most scrutinized is Eco-localism. Within this Eco-localism the Schumacherâs idea of \"sustainable economics\" has its most central influence. Eventhough, we still need to explore further some practical models and experiences of Eco-localism in the grassroot level. Regardless of its limitations in practical terms, Eco-localism as a system of ideas remain interesting and important alternative to be studied and used as a sharp analysis tool of the diverse practices of looting and exploitation by the regime of market fundamentalism. [abw]